The role and evaluation of parental medical activity in the prevention of chronic gastrointestinal diseases in children - Vorontsova, Tamara; Kobyliukh, Kateryna; Petrenko, Anastasia; Mudryk, Uliana; Dzhyvak, Volodymyr (The Ukrainian Scientific Medical Youth Journal, 2025)
Chronic gastrointestinal diseases in children represent a significant medical and social issue characterized by long-lasting conditions, periodic flare-ups, and a substantial decline in the quality of life. These conditions not only impact physical health but also interfere with educational performance, physical activity, and emotional well-being, ultimately affecting the child’s overall development. The management and outcome of these diseases heavily rely on the involvement of parents, including their ability to seek timely medical care, ensure adherence to prescribed diets and pharmacological treatments, maintain health records, and organize psychological support for their child. In this context, the role of parental medical activity is of crucial importance in preventing complications, managing symptoms, and improving the child’s overall quality of life. The purpose of this study was to evaluate the level of medical involvement among parents of children with chronic gastrointestinal disorders, identify factors influencing this involvement, and assess its significance in the prevention, treatment, and enhancement of the child’s quality of life. To achieve this, a cross-sectional survey was conducted involving 80 children aged 6 to 17 years, all registered with a dispensary for chronic gastrointestinal conditions, including gastritis, peptic ulcer disease, and irritable bowel syndrome. The survey included 47 questions divided into seven thematic areas: socio-demographic information, the course of the disease, awareness and interaction with healthcare services, prevention, psycho-emotional status, social support, and school or kindergarten adaptation. The responses were evaluated using a 1-3 point scale, with the total score used to categorize parental medical activity levels as low, moderate, good, above average, or high. The results indicated that 10% of parents had low activity levels, 22.5% demonstrated moderate involvement, 36.2% showed good activity, 21.3% had above-average activity, and 10% exhibited high engagement. In total, 67.5% of parents displayed a sufficient level of medical activity, while 32.5% showed low or moderate involvement. The areas where parents excelled included adherence to medical prescriptions (72.5%) and informing educational institutions about the child’s condition (65%). However, the most concerning aspects were the regular maintenance of medical records, which only 22.5% of parents managed effectively, and participation in psychological or social programs, which was less than 15%. These findings suggest that the psychosocial component of care remains undervalued by many families. Additionally, parental activity varied significantly depending on the educational and socio-economic status of the family. The study concluded that parental involvement in medical care plays a vital role in the prevention and treatment of chronic gastrointestinal diseases in children. This involvement directly affects the child’s health outcomes, psychosocial development, and overall quality of life. Future initiatives should focus on enhancing parental awareness, improving family education on medical and psychosocial care, and increasing support for families with lower socio-economic status to ensure equitable and effective management of chronic gastrointestinal conditions in children.